Mating strategy of Oecophylla smaragdina (Hymenoptera: Formicidae) in northern Australia. Issue 3 (13th November 2015) - Nielsen, Mogens Gissel; Peng, Renkang; Offenberg, Joachim; Birkmose, Dorthe
Abstract: The aim of this study was to elucidate the mating strategy of O ecophylla smaragdina (Fabricius, 1775) and to clarify the factors that related to the nuptial flight. The nuptial flight was investigated over three seasons in the Darwin area, Australia, in which a total of 19 swarmings were observed. All swarmings were observed on days where no rain fell before 15:00 h, and with wind speed ≤18 km/h. On days of swarming air pressure was significantly higher (mean ± SD: 1009.3 ± 1.6 hPa) than on rainless days without swarming (mean ± SD: 1006.9 ± 1.2 hPa). Several swarmings took place during the season, and the production of alate queens occurred more or less continuously over a period of at least 2 months. Therefore, the number of individuals in each swarming depends on the time elapsed since the last swarming. Swarming commenced with males gathering on the external surfaces of nests at sunrise, and about 15 min later they started departing, which took about 10 min. When the males commenced flying the females came out of the nests. When most males had flown, the females started flying, which also took about 10 min. Both males and females flew straight up towards an opening in the canopy. After swarming, alate queens were observed coming down to the canopy after 15–20 min. No queens were found in artificial queen traps 2 h after swarming. A few queens were observed flying around 13:00 h, and later in the afternoon many fertilised queens were found in queen traps. From field observation and laboratory experiments, we conclude that it is most plausible that alate queens meet the males in the air, proceed to the tree canopy to conclude the mating, and then after midday the mated alate queens fly individually to find a nesting site.